How do 10-camphorsulfonic acid, silver or aluminum nanoparticles influence optical, electrochemical, electrochromic and photovoltaic properties of air and thermally stable triphenylamine-based polyazomethine with carbazole moieties?. (10th December 2015) - Iwan, Agnieszka; Boharewicz, Bartosz; Tazbir, Igor; Filapek, Michal; Korona, Krzysztof P.; Wróbel, Piotr; Stefaniuk, Tomasz; Ciesielski, Arkadiusz; Wojtkiewicz, Jacek; Wronkowska, Aleksandra A.; Wronkowski, Andrzej; Zboromirska-Wnukiewicz, Beata; et al.
Abstract: Organic (10-camphorsulfonic acid, CSA), organic-inorganic (Ag-poly(vinylpyrrolidone), Ag-PVP with 10 and 20 nm size of Ag) or inorganic (Al, 18 nm) compounds were applied as new components of active layer in bulk heterojunction polymer solar cells based on a new polyazomethine (PAZ-Car-TPA) resulting in significant change of optical and electrical properties. Moreover, colloidal Ag (100 nm) and Ag-PVP in aqueous solution (10 nm) were tested as an addition to the hole transporting layer based on PEDOT:PSS in polyazomethine solar cells. CSA added to PAZ-Car-TPA decrease its energy gap from 1.91 to 1.20 eV and causes a significant bathochromic shift of the maximum of absorption band along with the change of the polymer color from yellow to red (electrochromic behavior). Photoluminescence maximum of PAZ-Car-TPA protonated with CSA showed 120 nm redshift from 500 to 620 nm in comparison to undoped PAZ-Car-TPA. HOMO-LUMO of PAZ-Car-TPA and its mixture with CSA were analyzed by cyclic voltammetry and quantum mechanical calculations using Density Functional Theory method. Refraction index and extinction coefficient of PAZ-Car-TPA and its mixtures with PC71 BM as well as Ag or Al nanoparticles were investigated taking into consideration various thickness of polymer layer. The power conversion efficiency of the ITO/PEDOT:PSS/PAZ-Car-TPA:PCBM:CSA/Al device was five time higher than that of the device based on PAZ-Car-TPA:PCBM. Such an enhancement was found to be primarily due to the increase of the short-circuit current, suggesting that the charge collection increases upon the incorporation of CSA in the active layer. Moreover, presence of Ag-PVP (20 nm) or Al (18 nm) in device increased short circuit current of the constructed polymer solar cells. Additionally, devices were tested by external quantum efficiency measurements and electrochemical impedance spectroscopy in dark and under illumination. The polymer solar cell with PAZ-Car-TPA as donor in active layer showed good stability over 600 hours, when stored in a climatic chamber.